Writing studies research in practice methods and methodologies - Nickoson, Lee, 1967-; Sheridan, Mary P., 1966- (Carbondale : Southern Illinois University Press, 2012)
An essential reference for students and scholars exploring the methods and methodologies of writing research. What does it mean to research writing today? What are the practical and theoretical issues researchers face when approaching writing as they do? What are the gains or limitations of applying particular methods, and what might researchers be overlooking? These questions and more are answered by the writing research field's leading scholars in Writing Studies Research in Practice: Methods and Methodologies. Editors Nickoson and Sheridan gather twenty chapter
18. The Role of Activity Analysis in Writing Research: Case Studies of Emerging Scholarly Communities by Mike Palmquist, Joan Mullin, and Glenn Blalock19. The Ethics of Conducting Writing Research on the Internet: How Heuristics Help by Heidi A. McKee and James E. Porter; After Words: Postmethodological Musings by Rebecca J. Rickly; Contributors; Index; Back Cover
Description based upon print version of record.
English
Includes bibliographical references and index.
Keywords: English language -- Rhetoric -- Study and teaching; Report writing -- Study and teaching